Exploring the Potential Campus-Level Impact of Online Universal Sexual Assault Prevention Education. Issue 5 (March 2021) - Zapp, Daniel; Buelow, Robert; Soutiea, Lauren; Berkowitz, Alan; DeJong, William
Campus sexual assault is a long-standing challenge and continues to be a severe problem for American higher education. The present study examines the short-term impact of a widely utilized sexual violence prevention course for matriculating college students as a population-level prevention approach. The course focuses on correcting misperceptions of normative behavior, increasing students' likelihood to intervene in disconcerting situations, and encouraging empathy and support for victims. Participants were 167, 424 first-year college students from 80 four-year institutions who completed preintervention and postintervention surveys to assess changes in composite factor scores derived from 20 attitudinal, self-efficacy, and behavioral intention items. Employing the composite factor scores as dependent variables, individual ANOVAs were run for each of the institutions to test whether there were significant increases in mean factor scores. High percentages of institutions saw statistically significant increases ( p < .05) in self-reported ability and intention to intervene to prevent sexual assault and relationship violence (98%), empathy and support for victims (84%), and corrected perceptions of social norms (75%). Fewer schools saw significant reductions in endorsement of sexual assault myths (34%). These findings suggest that when implemented as a population-level intervention for all first-year college students, the prevention course can foster accurate perceptions of positive social norms, increase empathy and support for victims, and increase students' stated ability and intention to intervene.